2001
DOI: 10.1016/s0006-3495(01)75969-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of the Cytoplasmic Domain of the Anion Exchange Protein, Band 3, in Human Erythrocytes

Abstract: The rotational flexibility of the cytoplasmic domain of band 3, in the region that is proximal to the inner membrane surface, has been investigated using a combination of time-resolved optical anisotropy (TOA) and saturation-transfer electron paramagnetic resonance (ST-EPR) spectroscopies. TOA studies of rotational diffusion of the transmembrane domain of band 3 show a dramatic decrease in residual anisotropy following cleavage of the link with the cytoplasmic domain by trypsin (E. A. Nigg and R. J. Cherry, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 56 publications
3
23
0
1
Order By: Relevance
“…The results presented in this article showed the functional aspects of the anion channel protein in horse. As previously observed in other species, 29,15,30 the structural integrity of band 3 has a close relationship with the anion transport in horse too. The different experimental conditions, in fact, reflect in alterations, which concern the structure of the membrane in all its components and this also influences sulfate influx.…”
Section: Discussionsupporting
confidence: 85%
“…The results presented in this article showed the functional aspects of the anion channel protein in horse. As previously observed in other species, 29,15,30 the structural integrity of band 3 has a close relationship with the anion transport in horse too. The different experimental conditions, in fact, reflect in alterations, which concern the structure of the membrane in all its components and this also influences sulfate influx.…”
Section: Discussionsupporting
confidence: 85%
“…Rotational relaxation studies of Cherry and colleagues 45 demonstrated that both populations were mobile, but that one exhibited relatively unrestricted rotation and the other displayed restrained, yet measurable rotation. Subsequent studies by Beth and coworkers 46 showed that the skeletally attached band 3 can rotate through an angle of 73°, probably because of the flexibility of the junction between the cytoplasmic and membrane-spanning domains of band 3. Data of Golan et al 47 have further demonstrated that depletion of ankyrin releases the less mobile population from its rotational restriction and that the rotational and lateral diffusion of band 3 are independently regulated, the former by protein interactions at the cytoplasmic surface of the membrane, and the latter by the spectrin content of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…We also labeled Band 3 on the RBC membrane with eosin‐5‐maleimide (EMA) to perform time‐resolved phosphorescence anisotropy (TPA) and fluorescence resonance energy transfer (FRET) experiments on the same 5 RBC units on Days 0, 12, 20, 29, 42, and 49 of cold storage. TPA has previously been shown to resolve distinct populations of Band 3 oligomeric complexes in the RBC membrane and is thus a powerful spectroscopic tool to determine the effect of RBC storage on the organization of membrane proteins 13,14 . Fluorescence resonance energy homotransfer is an independent (compared to TPA) technique that also detects large changes in the organization of Band 3 in the RBC membrane 15 .…”
mentioning
confidence: 99%